Influence of Growth Regulators on Root and Shoot Characters of Onion - Ud-Deen, MM; Kabir, G (Journal of Bio-Science, 2011)
Context: The growth behaviour and yield of any crop plants are governed by their genetic potential, climatic conditions and the supply of nutrients. Specific control of these processes can be done by the application of plant bioregulators of natural or synthetic origin. Objectives: The aim of the present investigation was to study the effect of different plant growth regulators on root and shoot emergence, and root and shoot length of onion. Materials and Methods: Onion. var "Taherpuri" was used as plant material and four growth regulators namely GA3, Uniconazol, CCC and 2,3,6-TBA along with water as control with different concentration viz. 100, 150, 200, 250 and 300 ppm were used as treatment. Onion bulbs were placed on vials containing different doses of growth regulators. Data recorded on root and shoot emergence and their lengths after different days of setting the experiment. Results: Higher concentrations of uniconazole necessitated maximum days for root and shoot emergence whereas GA3 required minimum days. Root length decreased gradually with increasing the concentrations of all the growth regulators at different days of emergence. Higher concentrations of GA3 produced longest shoot whereas same concentrations of uniconazole produced the shortest than the lower ones at different days of emergence. The highly significant and negative correlation was found between days to root emergence and shoot length and between days to shoot emergence and shoot length but highly significant and positive correlation was found between root length and shoot length. Conclusion: GA3 required minimum days to root and shoot emergence and promote the vegetative growth of onion whereas uniconazole and CCC are retards and 2,3,6-TBA shows a little retarding effect. Key words: Growth regulators; Root and shoot characters; Onion DOI: 10.3329/jbs.v17i0.7101 J. bio-sci. 17: 51-55, 2009